Analisis Optimalisasi Pengelolaan Dana Desa Untuk Kepuasan Masyarakat Di Desa Teluk Piai Kecamatan Kualuh Hilir Kabupaten Labuhanbatu Utara - Siregar, Maria Santia; Fadhila Rahma, Tri Inda; Kusmilawaty, Kusmilawaty (Universitas Labuhanbatu, 2022)
Along with the development of the economy in Indonesia, the government issued the Village Fund Allocation (ADD) program to improve community service facilities, in the form of meeting basic needs, strengthening village institutions and other activities needed by village communities by making decisions through deliberations. This research was conducted in Teluk Piai Village, Kualuh Hilir District, Labuhan Batu Utara Regency, using a qualitative method with a descriptive approach. The purpose of this study is to provide an overview of the implementation and optimization of village fund management for community satisfaction. The description results are obtained by comparing Permendagri No. 113 & 114 of 2014. The results of this study are that ADD management has not been carried out in a transparent and accountable manner because not all information regarding ADD allocation is conveyed to the public, both those that have been implemented and those that have not been implemented, so that the community does not know what obstacles and obstacles are experienced by village government in allocating Village Funds, and it can be concluded that the Management of Village Fund Allocations in Teluk Piai Village is Not Optimal.